Clinical and physiological evaluation of free-ranging snow leopards immobilized with ketamine-xylazine in emergency situations - Talukdar, Animesh; Bhasin, Anchal; Patel, Dimpi; Raina, Pankaj; Tonde, Prasad; Savita, Prateek (Frontiers in Veterinary Science, 2025)
The current study presents data on the immobilization and physiological responses of 26 distressed free-ranging snow leopards (Panthera uncia) in the trans-Himalayan regions of Ladakh, India, spanning three years from October 2020 to December 2023. Ketamine and xylazine were utilized in a drug mixture for rescue, rehabilitation, health assessment, and other capture purposes, with average doses of 6.535 ± 0.93 mgkg−1 and 1.937 ± 0.41 mgkg−1 of body weight, respectively. The average induction occurred at 3.85 ± 1.8 min. Respiratory rate, rectal temperature, and heart rate were monitored periodically post-induction, all remaining within clinically acceptable ranges. Following an average recumbency period of 70.69 ± 16.56 min, immobilizations were reversed using intramuscular injections of Yohimbine at 0.147 ± 0.03 mgkg−1 of body weight, leading to complete recovery within an average time of 24.92 ± 7.08 min. Our findings suggest that the ketamine and xylazine mixture represents a safe and effective method for immobilizing snow leopards, particularly in emergency scenarios.